Determinants of payout choice between open market repurchase, tender offer repurchase and special dividends - Urvashi Varma; Raveesh K; Alka Munjal (Cogent Economics & Finance, 2021)
The paper aims to identify the variables contributing to special payouts considering open market repurchase, tender offer repurchases, and special dividends. A multinomial logit model has been used to investigate the choice of payout out of 754 payout announcements made between 2004 and 2017 in India. The study investigates agency cost, shareholder heterogeneity, clientele effect, distribution size, misvaluation, and takeover threat. The MNL results suggest that open market repurchase is chosen when the takeover threat is high, firms are significant, or in case of undervaluation of firms. Tender offer repurchase is preferred in high agency cost, high takeover threat, low shareholder heterogeneity, and undervaluation. The study further investigates the nature of ownership in terms of a business group affiliated and standalone firms. The result of the study suggests the nature of ownership impacts the choice of dividend payout choice. Group affiliated firms are driven by clientele effect and distribution size, and in standalone firms' agency and shareholder heterogeneity holds. The Bayesian approach which is based on the combination of previous information and the current data available is used in the study for MNL. The findings suggest that payout choices of open market repurchase and tender offer repurchase over special dividends are based on misvaluation and shareholder heterogeneity.
Keywords: 330; multi nominal logit; open market repurchase; payout policy; tender offer repurchase